Nutrition label design and its effect on purchase intentions through readability considering consumer nutrition knowledge - Escaño, Ignacio Luis S. (Animo Repository, 2021)
Nutrition labels are the only accurate source of information of a product’s nutritional contents. They are intended to serve as a guide for consumers in selecting their food. However, these labels can only be effective if consumers read them. An identified gap on nutrition label use among consumers has raised concerns on the label’s need for improvement. One way of improving them is through their design as this was found to have a significant influence on consumer purchasing behavior. However, current international guidelines on nutrition labels are only concerned with the information displayed. There is no set standard for its design. Additionally, the consumer’s nutrition knowledge must also be considered to narrow the impact that various nutrition label designs have. This could help in increasing the effectiveness of the labels in positively influencing consumers with their purchase intention. In this study, the four factors incorporated were nutrition label design, readability, consumer nutrition knowledge, and purchase intention. Readability was hypothesized to mediate the effect of nutrition label design factors to purchase intention, whereas nutrition knowledge was hypothesized as a moderator of readability to purchase intention. The design factors tested were font size, highlighting critical information, and background color. The objective of this study is to formulate guidelines for nutrition label design to have a positive influence on purchase intention through readability. This is done through determining which design factors are significant to the consumer’s purchase intention, analyzing both the mediating role of readability and the moderating role of nutrition knowledge. A total of 320 participants took part in this study which were all literate Filipino consumers of four-side seal sachet products. The main experiment was done through an online survey that includes a photo and video of the sachet product with the nutrition label and a series of questions pertaining to the label. A total of eight surveys, each containing different combinations of the nutrition label design factors, were randomly assigned to each participant. Post-survey interviews were also conducted with willing participants for additional insights and information. A pilot experiment was first conducted to test the process and reliability of the questionnaire. The data obtained from the main experiment was then analyzed through structural equation modeling (SEM). From the results of the experiment, it was seen that the design factors of font size and background color are recommended. Both factors were found to have an indirect effect on purchase intention through readability and a positive effect on purchase intention. Participants noted that increasing font size for calories (8pt) helped emphasize this important component of the label while having a background with a higher color contrast ratio of 21:1, more clearly displays the nutrients allowing them to be easily evaluated. Additionally, nutrition knowledge was found to moderate these two indirect effects through moderated mediation. The indirect effects of font size and background color on purchase intention are more profound among people with lower nutrition knowledge compared to the population with higher nutrition knowledge. The findings of this study can help food manufacturers implement design guidelines for nutrition labels. Additionally, government regulatory bodies such as the Food and Drug Administration (FDA) can also use them to create a standard nutrition label design. The findings highlight that nutrition label design should focus on increasing readability as this was found to mediate the relationship between the design factors and purchase intention. Lastly, the findings of this research provide insights on the importance of considering the varying levels of nutrition knowledge consumers have when creating nutrition label designs.